Case-Based Discussion: Hypertension - Jenny Fortun; Rebecca Toonkel; Yerko Berrocal (Association of American Medical Colleges, 2015)
Abstract Introduction Experienced health physicians must synthesize and integrate information from multiple sources and disciplines. In order to foster this skill, undergraduate medical curricula must provide ample opportunities for guided practice, particularly in the earlier years of training. Case-based discussions (CBD) have emerged as an effective method to promote student learning and satisfaction. Different methodologies of CBD-teaching have been used to teach physiology with positive outcomes, including the promotion of better understanding of integration of physiological systems, and enhanced student performance when compared to lecture alone. This case was created in order to provide an opportunity to integrate physiology with clinical skills and to introduce students to elements of pathophysiology and clinical reasoning. Methods This 2-hour CBD was implemented in a first-year physiology course for undergraduate medical students. Prior to this CBD session, students learned basic principles of cardiovascular and renal physiology, the function of the autonomic nervous system, and acid-base homeostasis. The case is about a 72-year-old man with hypertension who is ultimately diagnosed with renal artery stenosis. Students were expected to explain the physiology of blood pressure control and to use their basic science knowledge as a framework to discuss a clinical presentation of secondary hypertension. In addition, to promote self-directed learning, students were asked to complete a clinical inquiry activity. As a group, students identified additional areas of basic or clinical interest and worked together to explore and answer their own questions. Results Overall, the case was well received and students feel that it significantly contribute to their learning (54% of students strongly agree and 33% of students agree). Discussion We are satisfied with the student responses on surveys and examinations. The small-group format provides the students with the opportunity to meet their learning needs and to receive individual feedback; it also allows faculty to identify students at risk. In our experience, the major limiting factor is the need to have a large number of adequately trained small-group facilitators to equalize the experiences between groups. It is our goal to expand this approach throughout the first year.